O ensino de química e a Língua Brasileira de Sinais - Sistema SignWriting (LIBRAS-SW): monitoramento interventivo na produção de sinais científicos - Costa, Edivaldo da Silva (2014)
The main objective of this research was to produce chemical signals in Brazilian Sign Language written in SignWriting system (BSL-SW) to support building for scientific and deaf students in education and scientific concepts inclusion process. Furthermore, variations showed some signs researched, made a mediator, when possible, the scientific language interface with quiremic composition of chemical signals expressed in BSL terminologies and writing signs in SW-Edit computational system. This research contributed to a further deepening of the studies on the teaching of chemistry in BSL and interdisciplinary scientific knowledge areas, in addition to being a resource for chemistry teachers, educational interpreters and deaf students BSL. The methodology chosen was based on the assumptions of action research. The field research was a room multifunctional resource linked to a public school of the state schools located in Itabaiana (SE). The main results point to the need of production and expansion of vocabulary terms of technical-scientific chemical signals in BSL to assist in the conceptual meaning and training by and for deaf students process. It turned out though the directionality problem and dactilologic cause interference linguistic marks in the mediation of the symbolic system for deaf students process. In this research, one hundred and thirty signals were collected and mapped hundred and five and twenty five produced. It was concluded that the process of producing signs of Chemistry by and for deaf students remains a scientific field of study and research area to be even better and more exploited by teaching professionals, a deeper analysis of the structural composition is necessary internal specialized lexicon that refers to the fields of linguistics, especially semantics. The use of the signs represented more integrally SignWriting the idea of movement of visual- spatial language, as is the case of BSL, as the fossil images of dictionaries and books representing the motion of the signals often hinder their implementation making it necessary to the use of video that is not always possible.